2017
DOI: 10.1186/s12891-017-1834-4
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of loss of correction after posterior wedge osteotomy in ankylosing spondylitis-related thoracolumbar kyphosis: a minimum of five-year follow-up

Abstract: BackgroundShort-term studies have demonstrated good surgical outcomes after pedicle subtraction osteotomy (PSO) in ankylosing spondylitis (AS) patients, but there is a paucity of literature focused on middle-term results, especially regarding patterns of loss of correction. The objective of this study is to assess the durability of surgical outcomes and the patterns of loss of correction in thoracolumbar kyphosis secondary to AS following lumbar PSO with over 5-year follow-up.MethodsWe performed a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The SVA decreased from approximately 171–174 mm before the surgery to average 59 mm in the PSO group and 63 mm in the VCD group after surgery and maintained till the final follow-up. Despite the immediate satisfactory surgical results, mild loss of correction of GK was observed in both groups in the long-term follow-up with no significant difference, which was in line with the previous studies [7, 14]. However, different from Qiao’s study [14], no significant changes were observed in the correction loss of lumbar lordosis.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The SVA decreased from approximately 171–174 mm before the surgery to average 59 mm in the PSO group and 63 mm in the VCD group after surgery and maintained till the final follow-up. Despite the immediate satisfactory surgical results, mild loss of correction of GK was observed in both groups in the long-term follow-up with no significant difference, which was in line with the previous studies [7, 14]. However, different from Qiao’s study [14], no significant changes were observed in the correction loss of lumbar lordosis.…”
Section: Discussionsupporting
confidence: 88%
“…In Zhu’s study [7], loss of correction in the GK of SPOs technique (3.9°) and PSO technique (2.4°) was identified 2 years after surgery. More recently, Mu [14] conducted a retrospective research in PSO-treated AS patients using comprehensive methods in analyzing the radiographic parameters and found a worsening of GK (2.82°) combined with decreased LL (3.77°) at the last visit of 6.9 years postoperatively. To our best knowledge, it remains unclear of the difference between PSO and VCD techniques on correction loss in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This higher possibility of correction loss for patients in NBG may be due to the fact that patients in this subgroup mostly had earlier forms of AS with underlying active inflammation. And their osteoproliferation process progressed during follow-up, developing collapse of proximal and distal discs, decreasing the mobility of non-fused segments, increasing the kyphotic angle of non-instrumented segments involved in the global kyphosis, and finally detracting from the initial correction [ 24 , 30 ]. This was also mirrored by the fact that 20.5% of the patients in NBG developed bridging syndesmophytes at the neighboring disc level by the ultimate follow up.…”
Section: Discussionmentioning
confidence: 99%